The reality of the professional learning communities of secondary school principals in Hail from the teachers' point of view - Al-Shammari, Mona Naif (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the reality of the professional learning communities of secondary school principals in Hail from the teachers' point of view, and the study relied on the descriptive analytical approach, and the study community consisted of (877) teachers, where the questionnaire was applied to a random sample of (266) teachers Among the teachers of secondary schools in Hail City, and the results of the study concluded that the reality of the practice of vocational learning societies came high in the total degree of the dimensions of the study and in each of them, and the results also showed that there are no statistically significant differences between the averages of the study sample responses about the reality of professional learning societies attributed For the variables of the scientific qualification and the number of years of service in teaching, and the study recommended the need to provide all the supportive conditions for achieving vocational learning societies in public education schools.
Keywords: professional learning communities; secondary school